MEDIA EFFECTS OF AFFAIRS IN â€œLAYANGAN PUTUSâ€ SERIES (STUDY ON SINGLE WOMEN IN BANDUNG CITY) - Alicia Achma Syafir; Maulana Rezi Ramadhana (Syntax Corporation, 2022)
This study discusses the effects of the media on infidelity in the layangan putus series. The purpose of this research is to find out the media effect of layangan putus series on the affair of unmarried women in Bandung. This study uses a qualitative research method with a naturalistic approach in which the researcher wants to describe how the effect of the serial media effect on the affair of women who have never been married in Bandung. Data collection techniques were carried out by observing and interviewing women who had never been married in Bandung. The results of the study show that to prevent infidelity, unmarried women experience emotional feelings and feelings of anxiety resulting from the media effect of